2015
DOI: 10.3390/ijms161025788
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Response to Oxidative Stress in Insects—An Update

Abstract: Insects, like other organisms, must deal with a wide variety of potentially challenging environmental factors during the course of their life. An important example of such a challenge is the phenomenon of oxidative stress. This review summarizes the current knowledge on the role of adipokinetic hormones (AKH) as principal stress responsive hormones in insects involved in activation of anti-oxidative stress response pathways. Emphasis is placed on an analysis of oxidative stress experimentally induced by variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 142 publications
1
99
0
8
Order By: Relevance
“…Kodrík et al (2015) suggest that FOXO confers oxidative-stress resistance via the transcriptional upregulation of genes encoding anti-oxidative enzymes. Our study suggests that FOXO also influences stress resistance via JH signalling and by regulating DA levels, which affect resistance to heat and nutritional stresses (Gruntenko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Kodrík et al (2015) suggest that FOXO confers oxidative-stress resistance via the transcriptional upregulation of genes encoding anti-oxidative enzymes. Our study suggests that FOXO also influences stress resistance via JH signalling and by regulating DA levels, which affect resistance to heat and nutritional stresses (Gruntenko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, AKHs are pleiotropic in nature and are involved in many metabolic activities including various aspects of the defense and antistress responses (Gäde et al, 1997;Kodrík, 2008). Thus, AKHs enhance food intake and digestive processes in the insect gut (Bil, Broeckx, Landuyt, & Huybrechts, 2014;Bodláková, Beňová, & Kodrík, 2018;Kodrík, Vinokurov, Tomčala, & Socha, 2012), stimulate general locomotion (Socha, Kodrík, & Zemek, 1999), participate in the activation of antioxidant mechanisms (Kodrík, Bednářová, Zemanová, & Krishnan, 2015;Kodrík, Krishnan, & Habuštová, 2007), and interact with the cellular and humoral immune systems (Goldsworthy, Opoku-Ware, & Mullen, 2002).…”
mentioning
confidence: 99%
“…AKH is an insect analog of the human hormone glucagon (Gáliková et al, 2017). The AKH/AKHR signaling plays crucial roles in energy mobilization (Galikova et al, 2015), antioxidative stress reactions (Kodrik et al, 2015), anti-obesity, and appetite regulation (Gáliková et al, 2017). Interestingly, our results indicated that AKH/AKHR signaling changed in response to changes in the GMF intensity in 5th instar N. lugens nymphs.…”
Section: Glucose Levels Of 5th Instar Nymphsmentioning
confidence: 71%
“…Additionally, recent computational work suggests that [FAD˙−-HO 2˙] or [FADH˙-O 2˙− ] can be alternative radical pairs at the origin of magnetoreception in Crys (Mondal and Huix-Rotllant, 2019), and ROS levels have also been shown to be sensitive to the changes in magnetic field intensity (Sherrard et al, 2018;Van Huizen et al, 2019). Moreover, it is well documented that ROS are critical in the regulation of energy metabolism and food intake due to their versatile roles in mediating the expression of vertebrate NPY (homolog of invertebrate NPF), glucose levels (Drougard et al, 2015) as well as the AKH/AKHR pathway (Kodrik et al, 2015). Therefore, another pathway that could explain GMF-involved appetite regulation is likely to be affected by ROS.…”
Section: Glucose Levels Of 5th Instar Nymphsmentioning
confidence: 99%